Mirounga angustirostris Gill 1866 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
3. Northern Elephant Seal Mirounga angustirostris French: El ¢phant-de-mer boréal / German: Nordlicher See-Elefant / Spanish: Elefante marino septentrional Other common names: Northern Sea Elephant Taxonomy. Mirounga angustirostris Gill, 1866, “California.” Restricted by A. J. Poole and V. S. Schantz in 1942 to “St. Bartholomews Bay, lower California, Mexico.” Clarified by V. B. Scheffer in 1958 as Bahia Tortola (= Bahia San Bartolomé) 27° 39° N, 114° 51’ W, Baja California, Mexico.” This species is monotypic. Distribution. NE Pacific, Aleutian Is, Gulf of Alaska, and W coast of North America S to C Baja California (Mexico); occasionally to Hawaiian Is and Japan, and into the Bering Sea. Descriptive notes. Total length ¢.350-400 cm (males) and ¢.215-300 cm (females); weight ¢.1800-2500 kg (males) and 300-600 kg (females). Northern Elephant Seals are smaller that Southern Elephant Seals (M. leonina). Sexual dimorphism in body size and shape of Northern Elephant Seals develops at 3—4 years old. Newborn males and females are similarsize, with total length of ¢.115-125 cm and weight of 25-35 kg. Offspring are black at birth and until weaned at 25-28 days postpartum and then molt into a silver-gray pelage that fades to chocolate brown dorsally and tan ventrally. Juvenile and adult pelage is light tan ventrally and brown to dark brown dorsally. Eyes are relatively large in all seals, apparent adaptations for maximizing light gathering power when foraging at great depths. Nose of a male Northern Elephant Seals begins to elongate at puberty at 3-5 years old;it is a distinct elongated proboscis and distinct secondary sexual characteristic at physical maturity when a male is 8-10 years old. Males’ noses help resonate and amplify their pulsed threat vocalizations. Dentition is sexually dimorphic but adapted in both sexes for snatching and firmly grasping prey, which is evidently swallowed whole. Canine teeth of males are large and robust and function as offensive weapons during fights during the breeding season. Canine ...